Strategi Pemasaran Efektif Gula Semut di PT Pradja Agro Indoland - Cita Ayu Setia Ningsih; Erlyna Wida Riptanti; Rhina Uchyani Fajarningsih (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
PT Pradja Agro Indoland is an agribusiness company dealing with coconut commodities, including crystal sugar. Currently, coconut crystal sugar has high potency because of its benefits. Several coconut crystal sugar companies compete to market their products domestically and abroad. The increasingly tight industrial competition requires PT Pradja Agro Indoland to formulate appropriate marketing strategies to find a profitable marketing position. This research aims to identify internal and external factors in PT Pradja Agro Indoland's coconut crystal sugar marketing, formulate alternative coconut crystal sugar marketing strategies, and determine appropriate strategic priorities for PT Pradja Agro Indoland to implement in marketing coconut crystal sugar products. This research uses a descriptive method, with 14 critical informants determined by purposive sampling, where the key informants were the people who knew about the marketing of coconut crystal sugar in PT Pradja Agro Indoland. Data collection using the interview method was done from March to June 2024. Data were analyzed using analytical tools, including the IFE matrix, EFE matrix, IE matrix, SWOT matrix, and QSPM, to determine the priority strategy. The research results show that the main strength in marketing coconut crystal sugar at PT Pradja Agro Indoland is its FFL (Fair For Life) and ROC (Regenerative Organic Certified) certification and perfect product quality control. The main weakness of PT Pradja Agro Indoland is that factory employees do not have work continuity. The foremost opportunity of the external factor for PT Pradja Agro Indoland is many farmers. The primary threat is the difficulty of regenerating penderes farmers. The strategic priority that PT Pradja Agro Indoland can implement based on the QSP matrix analysis is to expand the target market.